2018
DOI: 10.1093/hmg/ddy093
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenome-wide association in adipose tissue from the METSIM cohort

Abstract: Most epigenome-wide association studies to date have been conducted in blood. However, metabolic syndrome is mediated by a dysregulation of adiposity and therefore it is critical to study adipose tissue in order to understand the effects of this syndrome on epigenomes. To determine if natural variation in DNA methylation was associated with metabolic syndrome traits, we profiled global methylation levels in subcutaneous abdominal adipose tissue. We measured association between 32 clinical traits related to dia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Amongst the 23 papers included in this systematic review, 19 papers reported studies on DNA methylation, 2 papers presented data on histone modifications and 2 papers conducted studies on lncRNAs. Of the 19 papers that reported data on DNA methylation in AT from individuals with MUHO, 8 papers performed targeted epigenome studies (52-59) and 11 papers reported genome-wide studies (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). The main findings on the targeted DNA methylation studies are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the 23 papers included in this systematic review, 19 papers reported studies on DNA methylation, 2 papers presented data on histone modifications and 2 papers conducted studies on lncRNAs. Of the 19 papers that reported data on DNA methylation in AT from individuals with MUHO, 8 papers performed targeted epigenome studies (52-59) and 11 papers reported genome-wide studies (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). The main findings on the targeted DNA methylation studies are summarized in Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…The majority of the DNA methylation epigenome-wide studies relied on an array-based methodology, while 2 studies used the Reduced Representation Bisulfite Sequencing (RRBS) method for identifying DMRs (60,66). Most studies included adjustments for age, sex and BMI in the analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…Differential methylation analysis. DNA from the twins was used to prepare RRBS libraries as described previously with minor modifications (14). The libraries were sequenced using an Illumina HiSeq4000 yielding more than 20 million reads for each twin.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation assay. Genomic DNA was isolated by standard phenol-chloroform extraction method and used as input to prepare RRBS libraries as described previously (14) with minor modifications. For each sample, 50-100 ng of purified genomic DNA was digested with 20 U of MspI (NEB, USA) at 37˚C o/n in the presence of RNase Cocktail Mix (Ambion, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The InDiMeT study proposes to achieve this by conducting detailed phenotyping and phenome measurements in a prospective manner in a high-risk population setting. Though animal studies have underlined the epigenetic changes in the adipose associated, few have investigated adipose epigenetics in humans and none in the context of adipose DNL dysregulation and T2DM [10][11][12] which will help to identify epigenomic dysregulation of adipose DNL in T2DM AT. Although DNA methylation signatures are specific to tissue and cell types, only ~38% of the DNA methylation probes have been reported to be differentially methylated in blood in a tissue-specific fashion, implying likelihood of the rest ~62% probes being conservatively methylated between blood and other tissues.…”
Section: Rationale and Specific Aimsmentioning
confidence: 99%